2020
DOI: 10.1093/chemse/bjaa028
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Qualities Evoked by Quinine, Sucrose, and Capsaicin Associate With PROP Bitterness, but not TAS2R38 Genotype

Abstract: Genetic variability in the ability to taste thiourea compounds has been studied for 80+ years. Over the last 3 decades, many studies have reported perceived intensity of concentrated propylthiouracil (PROP) associates with greater intensity from a broad range of stimuli, including nonbitter tastants, irritants, and retronasally delivered odorants. Thus, PROP phenotype has become a common measure of individual differences in orosensation. Much, but not all, of the phenotypic variation in PROP bitterness is expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
6
16
0
Order By: Relevance
“…Our finding that the WETT ® and the other taste tests evaluated in this study differentiated between PTC taster categories is in accord with earlier findings that subjects with greater sensitivity to PTC and related compounds [e.g.,] are also more sensitive to some representatives of the other basic taste qualities (Bartoshuk et al, 1998;Chang et al, 2006;Doty et al, 2017;Doty & De Fonte, 2016;Drewnowski et al, 1997;Keller & Adise, 2016;Webb et al, 2015). Such associations, however, are complex and need not be solely due to genetic factors (Nolden et al, 2020). Although somewhat unorthodox, the present study's categorization of the PTC bitterness intensity ratings into three groups based on responses to two different PTC strips provided a metric beyond just a singlestimulus-based characterization of tasters and non-tasters.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that the WETT ® and the other taste tests evaluated in this study differentiated between PTC taster categories is in accord with earlier findings that subjects with greater sensitivity to PTC and related compounds [e.g.,] are also more sensitive to some representatives of the other basic taste qualities (Bartoshuk et al, 1998;Chang et al, 2006;Doty et al, 2017;Doty & De Fonte, 2016;Drewnowski et al, 1997;Keller & Adise, 2016;Webb et al, 2015). Such associations, however, are complex and need not be solely due to genetic factors (Nolden et al, 2020). Although somewhat unorthodox, the present study's categorization of the PTC bitterness intensity ratings into three groups based on responses to two different PTC strips provided a metric beyond just a singlestimulus-based characterization of tasters and non-tasters.…”
Section: Discussionsupporting
confidence: 91%
“…A large sample size study (n > 1500) found a weak association between sweetness and PROP bitterness, suggesting that a bigger size sample is required to detect weak association with PROP [60]. A recent study confirmed that PROP bitterness was positively correlated with sweetness of sucrose [61]. However, some of the previous studies also indicated that there was no relationship between PROP sensitivity and sweet taste responsiveness [62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Meyerhof et al [54] sorted receptors into 4 groups, and both TAR2S4 and TAS2R14 were not in the same group as TAS2R38. The different responses in bitter taste receptors might explain why no relationship was found between PROP taster status and perceived bitterness intensity of Reb A, D, and M. Some studies suggested that PROP bitterness sensitivity influenced other oral sensations, such as sweetness [36,37,[57][58][59][60][61]. Drewnowski et al [36] found a weak and marginal significant difference in sweetness perception of sucrose and saccharin between PROP tasters and non-tasters, and the difference was more significant at lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-researched sensory segmentation of consumers is based on responses to the bitter compound 6-n-propylthiouracil (PROP). Responses to this compound, which are at least partly genetically determined [ 4 ], also reflect responses to other bitter compounds, as well as sweetness, sourness, and a variety of oral and odour irritant and textural attributes, in both solutions and foods/beverages [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%